Evaluation of Floor Pressure Distribution in Female Athletes With Tibial Internal Pressure Syndrome - Mojgan Rokninejad; Seyyedeh Hanniyeh Hashemi (Biyumikānīk-i varzishī)
Objective: Internal tibial pressure syndrome is one of the most common musculoskeletal disorders in athletes. Muscle imbalance in the dorsiflexor and plantar flexor muscles of the ankle in this syndrome may affect the distribution of plantar pressure in different parts of the foot. Therefore, the present study aimed to evaluate plantar pressure distribution in female athletes with tibial internal pressure syndrome. Methods: The statistical sample of this study, a comparative analytical study, consisted of 70 female athletes in the field of physical education in Tehran (including 35 subjects with tibial pressure syndrome and 35 healthy subjects in the age range of 18-22 years), which were randomly selected and purposefully selected. Plantar pressure values during walking between the experimental and control groups were assessed using a foot scan device in ten areas of the sole. The data of this study were analyzed using an independent t-test. Results: This study showed that the distribution of plantar pressure in the group with tibia internal pressure syndrome in 6 variables of the first toe, first metatarsus, second metatarsus, third metatarsus, midfoot, and heel was higher than the control group (P≤0.05). But the other measured variables of plantar pressure, which include the second to fifth toe, fourth metatarsus, fifth metatarsus, and the outer part of the heel, are not significant in both groups (P≥0.05). Conclusion: According to the results of this study, the hypothesis is supported that plantar pressure distribution may be higher in people with tibial internal pressure syndrome. This increase in plantar pressure can be due to excessive pronation of the ankle. Future studies should focus on the effects of therapies on reducing plantar pressure in people with the syndrome.